THE PARTICIPATION OF UZBEK PARTISANS IN THE LIBERATION OF THE TERRITORY OF THE FORMER SOVIET UNION (A CASE STUDY OF UKRAINE AND THE RSFSR) - Qosimov M. R. (TARIXIY TADQIQOTLAR, 2026)
This article examines the partisan movement on the territory of the USSR during the Second World War as a form of armed resistance to Nazi occupation. Drawing upon archival documentation, published primary sources, and historiographical studies from different periods, the paper analyzes the participation of individuals from Uzbekistan in partisan formations operating in the Byelorussian SSR, the Ukrainian SSR, and the western regions of the RSFSR. Particular attention is given to the incorporation of servicemen originating from Uzbekistan who escaped from prisoner-of-war camps into partisan structures, as well as to an assessment of their role in sabotage activities, intelligence operations, and other forms of resistance in the occupied territories. The study seeks to provide a comprehensive evaluation of their contribution within the broader framework of Soviet military history.